2021
DOI: 10.1038/s41598-021-99013-5
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of a mouthwash containing an antiviral phthalocyanine derivative on the length of hospital stay for COVID-19: randomised trial

Abstract: The risk of contamination and dissemination by SARS-CoV-2 has a strong link with nasal, oral and pharyngeal cavities. Recently, our research group observed the promising performance of an anionic phthalocyanine derivative (APD) used in a mouthwash protocol without photoexcitation; this protocol improved the general clinical condition of patients infected with SARS-CoV-2. The present two-arm study evaluated in vitro the antiviral activity and cytotoxicity of APD. Additionally, a triple-blind randomized controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 37 publications
(52 reference statements)
1
30
0
1
Order By: Relevance
“…A randomized clinical trial found that mouthwash containing CPC + Zinc and CHX resulted in substantial reduction of the SARS-CoV-2 viral load in saliva for up to 60 min after rinsing, whereas mouthwash with hydrogen peroxide (HP) resulted in a significant reduction for up to 30 min [ 41 ]. According to a study using an anionic phthalocyanine derivative (APD) in a mouthwash protocol, the mechanical action of the mouthwash containing a chemical with antiviral activity against SARS-CoV-2 may minimize patient symptoms and virus spread [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…A randomized clinical trial found that mouthwash containing CPC + Zinc and CHX resulted in substantial reduction of the SARS-CoV-2 viral load in saliva for up to 60 min after rinsing, whereas mouthwash with hydrogen peroxide (HP) resulted in a significant reduction for up to 30 min [ 41 ]. According to a study using an anionic phthalocyanine derivative (APD) in a mouthwash protocol, the mechanical action of the mouthwash containing a chemical with antiviral activity against SARS-CoV-2 may minimize patient symptoms and virus spread [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21] Since saliva was an important source of virus transmission during the pandemic, protective measures, such as the use of antiseptic gargles were adopted and recommended by several countries and organizations against SARS-CoV-2. 5,10,[21][22][23] Some studies have shown that the use of a mouthwash containing APD can reduce the viral load of SARS-CoV-2, acting as a therapeutic aid in reducing the severity and risk of COVID-19 transmission. 8-9, 22-24 These data corroborate the ndings of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…(94) and conivaptan targets viral non-structural protein 9 (Nsp9) (95). Phthalocyanine has been shown to be effective against preventing covid-19 in randomized trials (96). Bemcentinib has been shown to be effective against SC2 (97) and is being tested (trial NCT04890509) for efficacy in hospitalized covid-19 patients.…”
Section: Identifying Novel Potential Anti-sc2 Targets and Drugsmentioning
confidence: 99%